1996
DOI: 10.1016/0014-5793(96)00540-6
|View full text |Cite
|
Sign up to set email alerts
|

Light is required for efficient translation elongation and subsequent integration of the D1‐protein into Photosystem II

Abstract: The light dependence of translation and successive assembly of the D1 reaction center protein into Photosystem II subcomplexes was followed in fully developed chloroplasts isolated from the dark phase of diurnally grown spinach. The incorporation of synthesized D1 protein into Photosystem II (PSII) was analyzed by fractionation of radiolabeled unassembled protein and PSII (sub)complexes on sucrose density gradients. The ribosomes with attached nascent chains were recovered as pellets in the same gradients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The question of how FtsH complexes recognize the N-terminal tail of D1 has not been answered yet. Previous studies showed that translation of D1 and D2 is arrested in the mRNA elongation phase (Klein et al, 1988;van Wijk and Eichacker, 1996;Coló n-Ló pez and Sherman, 1998;Herranen et al, 2001;Tyystjä rvi et al, 2001). Interestingly, we found that dark conditions associated with protein synthesis inhibition caused a rapid decrease of D2 only in the ftsh2 background, because no change was detected in the wildtype, pdf1b, or pdf1b ftsh2 backgrounds.…”
Section: Discussionmentioning
confidence: 39%
“…The question of how FtsH complexes recognize the N-terminal tail of D1 has not been answered yet. Previous studies showed that translation of D1 and D2 is arrested in the mRNA elongation phase (Klein et al, 1988;van Wijk and Eichacker, 1996;Coló n-Ló pez and Sherman, 1998;Herranen et al, 2001;Tyystjä rvi et al, 2001). Interestingly, we found that dark conditions associated with protein synthesis inhibition caused a rapid decrease of D2 only in the ftsh2 background, because no change was detected in the wildtype, pdf1b, or pdf1b ftsh2 backgrounds.…”
Section: Discussionmentioning
confidence: 39%
“…For example, van Wijk and Eichacker (1996) observed that absence of light during translation leads to the increased accumulation of polysome-bound translational intermediate forms of D1, which indicates that light is required for efficient elongation of the D1 protein. The extent of incorporation of radiolabeled Met into the D1 protein and CP43 (Chl protein of 43 kD) decreased 3-fold in darkness, whereas the accumulation of the D2 reaction-center protein was unaffected by light.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, light was also required for the efficient incorporation of the D1 protein into the PSII core complex. In darkness, the newly synthesized D1 protein accumulated predominantly as unassembled protein or in PSII subcomplexes of less than 100 kD (van Wijk and Eichacker, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll a -dependent accumulation of plastidencoded chlorophyll a binding proteins is regulated at the cotranslational and post-translational levels (Klein and Mullet, 1986;van Wijk and Eichacker, 1996;Edhofer et al, 1998;Mühlbauer and Eichacker, 1998). During the first hour of illumination of etiolated barley, similar amounts of the mRNAs psbA , psbD , psbC , and psaA / psaB , which encode the photosystem chlorophyll apoproteins D1, D2, CP43, and P700A/P700B, respectively, remain associated with polysomes (Klein et al, 1988;Mullet et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other chlorophyll-associated proteins, including the nuclear-encoded chlorophyll a / b binding light-harvesting proteins (Bennett, 1981;Kuttkat et al, 1998), PSI chlorophyll proteins in Chlamydomonas (Herrin et al, 1992), and bacteriochlorophyll binding proteins of photosynthetic bacteria, are stabilized by chlorophyll (Dierstein, 1983). As shown indirectly by spectroscopy and by photochemical activity measurements, binding of chlorophyll a occurs within the first hour after illumination of etiolated barley (Egnéus et al, 1972;Wellburn and Hampp, 1979;Burkey, 1986;Ohashi et al, 1989;Franck, 1993); however, no direct evidence for chlorophyll a -dependent photosystem assembly has been reported.Chlorophyll a -dependent accumulation of plastidencoded chlorophyll a binding proteins is regulated at the cotranslational and post-translational levels (Klein and Mullet, 1986;van Wijk and Eichacker, 1996;Edhofer et al, 1998;Mühlbauer and Eichacker, 1998). During the first hour of illumination of etiolated barley, similar amounts of the mRNAs psbA , psbD , psbC , and psaA / psaB , which encode the photosystem chlorophyll apoproteins D1, D2, CP43, and P700A/P700B, respectively, remain associated with polysomes (Klein et al, 1988;Mullet et al, 1990).…”
mentioning
confidence: 99%